Walking the Line: A Fibronectin Fiber-Guided Assay to Probe Early Steps of (Lymph)angiogenesis. - Maria Mitsi; Martin Michael Peter Schulz; Epameinondas Gousopoulos; Alexandra Michaela Ochsenbein; Michael Detmar; Viola Vogel (PLoS ONE)
Angiogenesis and lymphangiogenesis are highly complex morphogenetic processes, central to many physiological and pathological conditions, including development, cancer metastasis, inflammation and wound healing. While it is described that extracellular matrix (ECM) fibers are involved in the spatiotemporal regulation of angiogenesis, current angiogenesis assays are not specifically designed to dissect and quantify the underlying molecular mechanisms of how the fibrillar nature of ECM regulates vessel sprouting. Even less is known about the role of the fibrillar ECM during the early stages of lymphangiogenesis. To address such questions, we introduced here an in vitro (lymph)angiogenesis assay, where we used microbeads coated with endothelial cells as simple sprouting sources and deposited them on single Fn fibers used as substrates to mimic fibrillar ECM. The fibers were deposited on a transparent substrate, suitable for live microscopic observation of the ensuing cell outgrowth events at the single cell level. Our proof-of-concept studies revealed that fibrillar Fn, compared to Fn-coated surfaces, provides far stronger sprouting and guidance cues to endothelial cells, independent of the tested mechanical strains of the Fn fibers. Additionally, we found that VEGF-A, but not VEGF-C, stimulates the collective outgrowth of lymphatic endothelial cells (LEC), while the collective outgrowth of blood vascular endothelial cells (HUVEC) was prominent even in the absence of these angiogenic factors. In addition to the findings presented here, the modularity of our assay allows for the use of different ECM or synthetic fibers as substrates, as well as of other cell types, thus expanding the range of applications in vascular biology and beyond.